ANALISIS MISKONSEPSI MATERI BILANGAN DESIMAL PADA BUKU PELAJARAN MATEMATIKA SISWA SMP KELAS VII - Alya Anggriani Sinaga; Nia Novita Insani Sinaga; Cintya Agatha Rumahombar; Putri Arga L. Munte; Wingston Leonard Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the types of misconceptions found in the presentation of decimal number material in grade VII junior high school mathematics textbooks. The research method used was qualitative with a content analysis approach. The data sources consisted of two officially published mathematics textbooks by the government, namely the 2017 revised Curriculum 2013 edition and the 2022 Merdeka Curriculum edition. Data were collected through documentation, misconception identification, and systematic note-taking, then analyzed through data reduction, categorization, interpretation, and conclusion drawing. The findings revealed five main types of misconceptions: (1) place value misconceptions; (2) misconceptions in comparing decimal numbers; (3) misconceptions in decimal operations; (4) misconceptions in converting fractions to decimals; and (5) misconceptions in understanding the equivalence of fractions and decimals. These findings indicate that textbooks still have the potential to generate misconceptions if not accompanied by sufficient conceptual explanations.